2007
DOI: 10.2139/ssrn.1016047
|View full text |Cite
|
Sign up to set email alerts
|

Seeking Opportunities: Migration as an Income Diversification Strategy of Households in Kakamega District in Kenya

Abstract: Migration and remittances are widely seen as major components of diversification strategies aimed at coping with risky environments in developing countries. The debate in the literature mainly concentrates on effects of and access to the strategy of migration. Against this background, the paper investigates patterns, determinants and the impact of internal migration on households based on data from a densely populated rural area in Western Kenya. The motivation behind migration is largely economic in kind. Acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…For example, some studies that have been conducted in Africa have attempted to identify the determinants of migration. The results of these studies indicate that migration decisions depend on positive urban-rural wage differences [27], education and migrant networks [28], the ecological vulnerability of communities [5], and employment opportunities in rural areas [7].…”
Section: Review Of Literaturementioning
confidence: 99%
“…For example, some studies that have been conducted in Africa have attempted to identify the determinants of migration. The results of these studies indicate that migration decisions depend on positive urban-rural wage differences [27], education and migrant networks [28], the ecological vulnerability of communities [5], and employment opportunities in rural areas [7].…”
Section: Review Of Literaturementioning
confidence: 99%
“…They found that migration relatively occurs in workers experiencing a positive income difference between urban and rural areas, showing that skilled workers make their own decisions to migrate to an urban area. Giesbert (2007) showed evidence from West Kenya that indicated that the tendency to migrate depends on education and the migrant network, but it is not related to household wealth. Ezra and Kiros (2001) found that individual members of a poor household, in terms of economic condition and in a community that is ecologically vulnerable in Ethiopia, tend to migrate more often than those from a less vulnerable area.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It helps them diversify income across members of the household, making the family less vulnerable to shocks like job loss or sudden sickness. Migration also helps diversify income over time, reducing the risk of dire lean periods for the whole household (Chen, Chiang, and Leung ; Giesbert ; Shonchoy ; Bignebat and Sakho‐Jimbira ; Marchetta ; Bryan, Chowdhury, and Mobarak ).…”
Section: The Effect Of Development On Migrationmentioning
confidence: 99%
“…It helps them diversify income across members of the household, making the family less vulnerable to shocks like job loss or sudden sickness. Migration also helps diversify income over time, reducing the risk of dire lean periods for the whole household (Chen, Chiang, and Leung 2003;Giesbert 2007;Shonchoy 2011; This too suggests that the effect of greater economic development on migration decisions can be complex. More stable and predictable economies can reduce the need to ensure against negative shocks, but as aspirations rise, so can the need for insurance.…”
Section: Greater Short-term Income Diversification Tends To Discouragmentioning
confidence: 99%